From Video-mediated Communication to Technologies for Collaboration: Reconfiguring Media Space - Heath, C.; Luff, P.; Sellen, Abigail (S. Emmott (Ed.) Information superhighways: Multimedia users and futures, London: Academic Press, 1995)
Despite the substantial corpus of research concerned with the design and development of media space, the virtual workplace has failed to achieve its early promise. In this paper, we suggest that a number of problems which have arisen with the design and deployment of media space, derive from their impoverished concept of collaborative work. Drawing from our own studies of video connectivity, coupled with analyses of work and interaction in real-world settings, we consider ways in which we might reconfigure media space in order to provide more satisfactory support for collaboration in organisational environments. [The future of the telephone will mean]...nothing less than a reorganisation of society — a state of things in which every individual, however secluded, will have at call every other individual in the community, to the saving of no end of social and business complications, of needless goings to and fro, of disappointments, delays, and a countless host of great and little evils and annoyances which go so far under present conditions to make life laborious and unsatisfactory. (Scientific American, 1880 p.16) That’s a funny kind of thing, in which each new object becomes the occasion for seeing again what we see anywhere; seeing people’s nastinesses or goodnesses and all the rest, when they do this initially technical job of talking over the phone. The technical apparatus is, then, being made at home with the rest of our world. And that’s a thing that’s routinely being done, and it’s the source for the failures of technocratic dreams that if only we introduced some fantastic new communication machine the world will be transformed. Where what happens is that the object is made at home in the world that has whatever organisation it already has. (Sacks, 1972 [1992] p. 548)